Movement`s analysis and weight transfer during the golf swing - Gryc, T.; Zahalka, F.; Maly, T.; Mala, L.; Hrasky, P. (Journal of Physical Education and Sport, 2015)
Golf swing is one of the most complicated of sport motions. The purpose of this study was complex evaluation of the golf swing, intra-individual stability of performance and relational analysis of selected parameters. To measure the kinematics of the golf swing we used 3D kinematic analyzer CODA Motion System and to measure weight transfer we used two force plates KISTLER. We evaluated selected spatial parameters of body motion and selected action force parameters (separately for left and right lower extremity). The golf swing was evaluated in eight separate events specified according to the golf club position. High intraindividual and interindividual performance stability was found during downswing phase of the golf swing in elite golf player`s sample. Interindividual variability during backswing phase was higher which indicated different timing of the swing between the players. High relation between golf club velocity and weight transfer was found and indicated that subjects (elite golf players) used weight transfer toward the target throughout the swing to produce extra energy to the ball. However, differences between subjects were found in weight transfer strategy during the golf swing and are related to the golf club speed.